How Does the Qur'anic Concept of Sunlight, Interpreted by Fakhr al-Din al-Razi, Integrate Theological Wisdom and Scientific Understanding in Sustaining Life? - Ali Mahfuz Munawar; H Halimatussadiah; R Rochmad; Ahmad Suharto; Muhamad Shofwan Muttaqin (QiST: Journal of Quran and Tafseer Studies, 2025)
Studies of the sun in Qur'anic scholarship have largely been fragmented and reductionist, focusing mainly on astronomical calculations or physical characteristics while neglecting the broader influence of sunlight on living beings and its theological significance. Existing research often treats the sun as a cosmic object or a temporal marker, without integrating classical Qur'anic exegesis with contemporary scientific knowledge. This condition reveals an epistemological gap between traditional tafsīr studies and modern scientific discourse, particularly within thematic Qur'anic interpretation rooted in the intellectual legacy of Fakhr al-Dīn al-Rāzī. This study aims to examine the Qur'anic concept of sunlight through the exegetical framework of Fakhr al-Dīn al-Rāzī, analyze its influence on humans, animals, and plants, and explore the divine wisdom behind its creation by engaging with modern scientific perspectives. Methodologically, this research employs a qualitative library-based design using a thematic (tafsīr mawdhū‘ī) approach combined with descriptive-analytical analysis. The primary source is al-Rāzī's Mafātīḥ al-Ghayb, which is critically contextualized with contemporary scientific literature in ecology, health sciences, and natural sciences. The findings indicate that al-Rāzī conceptualizes sunlight not merely as a physical source of illumination, but as a multidimensional divine sign. Sunlight functions as a source of life energy, a regulator of biological rhythms, a determinant of time, a contributor to human health, a driver of animal ecosystems, and a fundamental factor in photosynthesis and plant growth. These insights demonstrate a strong conceptual resonance between al-Rāzī's rational-philosophical exegesis and modern scientific principles, despite differing epistemological foundations. At the global level, this study contributes to strengthening religion-science dialogue, promoting ecological consciousness, supporting environmental sustainability, and advancing a holistic ethical framework for understanding the interconnected relationship between humanity, nature, and the Divine.